The prairie populist: How Stephen Harper transformed Canada. Issue 3 (December 2015) - Chwalisz, Claudia
Abstract : Sounding a note of warning for Europe's mainstream political parties, Claudia Chwalisz traces the rise of Stephen Harper and Canada's populist right‐wing Reform party, which she argues was able to capitalise on a public disenchantment with traditional parties that today is being felt in many European democracies.